Determination of content of indole alkaloids in cell biomass of Rauwolfia serpentina Benth. ex Kurz tissue culture - O. A. Bieda; I. I. Konvaliuk; L. P. Mozhylevska; S. S. Lukashov; V. A. Kunakh; S. M. Yarmoluk (Zaporozhye State Medical University, 2021)
Cardiovascular diseases are the most common human diseases, hence, the production of cardiological (in particular, anti-arrhythmic) medications from the natural sources is an ever-actual task. Rauwolfia serpentina Benth. is a tropical fruticose plant that is able to produce and concentrate indole alkaloids, especially ajmaline and its derivatives, which are the most effective medications against ventricular arrhythmia with low side effects. Aim of the study. Determination of the qualitative and quantitative content of indole alkaloids in cell biomass of Rauwolfia serpentina tissue culture, obtained by the prolonged in vitro growth. Materials and methods. Object: cell biomass of Rauwolfia serpentina tissue culture (K-27 strain), obtained by methods of long-term cell selection in vitro. Alkaloids content determination: TSQ Vantage LC-MS (ThermoFischer Scientific). Results. 20 indole alkaloids are found in cell biomass of Rauwolfia serpentina tissue culture (K-27 strain). The highest content is registered for ajmaline and its derivatives (0.690 % mass. for ajmaline). The contents of reserpine and yohimbine were found to be as low as 0.009 % and 0.020 %, respectively. Conclusions. It is established that the content of indole alkaloids is higher in K-27 strain in comparison to natural plant and is stable over more than 30 years of its growth. Total alkaloids content was found to be 2.8 % of dry cell biomass, and total ajmaline-type alkaloids content (including ajmaline) was found to be 1.6 % of dry cell biomass. In contrast, the total alkaloid contents in the natural plant material is reported to be in the range of 0.8-1.3 %.